Electronic structure of Mott-insulator CaCu3Ti4O12: Photoemission and inverse photoemission study. (September 2015) - Im, H.J.; Iwataki, M.; Yamazaki, S.; Usui, T.; Adachi, S.; Tsunekawa, M.; Watanabe, T.; Takegahara, K.; Kimura, S.; Matsunami, M.; Sato, H.; Namatame, H.; et al.
Abstract: We have performed the photoemission and inverse photoemission experiments to elucidate the origin of Mott insulating states in A-site ordered perovskite CaCu3 Ti4 O12 (CCTO). Experimental results have revealed that Cu 3 d –O 2 p hybridized bands, which are located around the Fermi level in the prediction of the local-density approximation (LDA) band calculations, are actually separated into the upper Hubbard band at ~1.5 eV and the lower Hubbard band at ~−1.7 eV with a band gap of ~1.5–1.8 eV. We also observed that Cu 3 d peak at ~−3.8 eV and Ti 3 d peak at ~3.8 eV are further away from each other than as indicated in the LDA calculations. In addition, it is found that the multiplet structure around −9 eV includes a considerable number of O 2 p states. These observations indicate that the Cu 3 d and Ti 3 d electrons hybridized with the O 2 p states are strongly correlated, which originates in the Mott-insulating states of CCTO. Abstract : Highlights: Mott-insulating states of CaCu3 Ti4 O12 have been investigated by PES and IPES. Mott-insulating states have been observed in Cu 3 d –O 2 p hybridized bands. Cu 3 d and Ti 3 d electrons hybridized with O 2 p states are strongly correlated.